Re-visioning the Mission of Health : A Global Invitation to Heal and Thrive in Crisis - Hayfron, David Nyansah; Kim, Kirsteen; Salvatierra, Alexia. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2026)
This volume is a global, multidisciplinary exploration of the church's mission of creating healthy individuals, families, communities and societies. Following the healing ministry of Jesus, Christians have assumed the availability of divine healing and spiritual well-being, internally and interpersonally. Contributors analyze diverse ministries of health and healing, from around the world and throughout the ages, through historical, theological, and practical lenses. These include desert monasteries; medieval hospices, and shrines; modern "medical missions"; "Christian health services"; contemporary psychological therapies; and Christian healers, who may use traditional medicines and reject biomedical intervention. This research shows how healing is integral to Christian faith and mission.